The bearing strength capacity perpendicular to grain of norway spruce – Evaluation of three structural timber design models. (15th February 2016) - Leijten, A.J.M.
Highlights: Current models to predict the compressive strength perp to grain are unreliable. Only one model based on yield slip-line theory is accurate. The V.d. Put model is the candidate for future building design code implementation. Abstract: The perpendicular to grain compressive strength of timber is known to be much lower than the strength parallel to grain. Many timber structures, however, rely on this property especially in bearings that occur frequently in building practice. The linear elastic–plastic behaviour of structural timber loaded perpendicular to grain has been a problematic issue for decades which is reflected in the differences between the prediction models in structural design codes over the world. This article concentrates on the evaluation of the strength predictive ability of three of the latest bearing models having an empirical, semi-empirical or physical background. On the bases of a large database of over 1000 test results covering eight practical load cases, it is shown that the accuracy and consistency of the physical model is the best, which makes it a potential candidate for the new generation timber design codes.